Rancang Bangun Aplikasi Workflow Seleksi Penerima Beasiswa Pada STIKES Yayasan Dr. Soetomo Surabaya Berbasis Web - Yason Novrianto; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2016)
STIKES Foundation Hospital Dr. Soetomo is a private university under the auspices of the Foundation Hospital Dr. Soetomo. To alleviate the cost of education, then STIKES Foundation Hospital Dr. Soetomo providing scholarships to students. In these scholarships there are problems ranging from a period very close to accreditation, there has been manipulation of data of the applicants and the unintegrated data in STIKES Foundation Hospital Dr. Soetomo.Based on the problems above, in this study the determination of an application made on STIKES Yasayan grantee Dr. Soetomo web based. With the application of the grantee problems that occur can be resolved. In the completion of this application using the Workflow as a reference in a flow system. This method is considered to provide information to each of the parties directly related to scholarships, other than that with this way each part can check the work of each section.Based on the results of testing and evaluation, the application can be designed and built in a timely complete the selection, appraisal and filling CPI data has can be automatically done because it is connected with the data of students who have been there before. The names of applicants who are selected for inspection by each relevant section of this scholarship reception so that each part can keep an eye on each other as part of the evaluation so that the data can be maintained registries.